1971
DOI: 10.1111/j.1365-2672.1971.tb02302.x
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Flora of the Rumen of Cows Fed Hay and High Cereal Rations and its Relationship to the Rumen Fermentation

Abstract: Summary. The rumen microbial population associated with feeding cows 3 rations, hay alone, 20% hay/80% flaked maize and 20% hay/80% rolled barley has been examined. The differences between the hay and the cereal rations were considerable but between the cereal rations only slight. Both cereal rations provoked & large drop in the proportion of butyrivibrios, and a rise in the proportion of selenomonads, peptostreptococci, lactobacilli and bifidobacteria. The importance of these and other changes occurring in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
2
2

Year Published

1971
1971
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(65 citation statements)
references
References 27 publications
5
56
2
2
Order By: Relevance
“…However, in practice, it is difficult to evaluate this scientifically, as no two feed ingredients are identical in all constituents bar starch and fibre. In the present study, there were also numerical differences in OM, ADF, ether extract and WSC between the two concentrate sources, all of which could alter rumen fermentation pathways within the rumen (Latham et al, 1971) and alter the ruminal microbial diversity (Flint et al, 2008).…”
Section: Feed Compositionmentioning
confidence: 55%
“…However, in practice, it is difficult to evaluate this scientifically, as no two feed ingredients are identical in all constituents bar starch and fibre. In the present study, there were also numerical differences in OM, ADF, ether extract and WSC between the two concentrate sources, all of which could alter rumen fermentation pathways within the rumen (Latham et al, 1971) and alter the ruminal microbial diversity (Flint et al, 2008).…”
Section: Feed Compositionmentioning
confidence: 55%
“…bovis were approximately 50 % lower in high-fibre than high-grain diets but these numbers were all within one log unit. These authors (Latham et al, 1971(Latham et al, , 1972) also demonstrated an increase in Lactobacillus numbers on high-grain diets. In contrast we observed a relative decline in Str.…”
Section: Discussionmentioning
confidence: 85%
“…bovis on high-forage diets, but the magnitude of this difference is usually less than one log unit. Latham et al (1971Latham et al ( , 1972 demonstrated that Str. bovis were approximately 50 % lower in high-fibre than high-grain diets but these numbers were all within one log unit.…”
Section: Discussionmentioning
confidence: 99%
“…A change from a fermentation characterized by a high proportion of butyric acid to one in which propionic acid is a major product has been related to the elimination of protozoa from the rumen (Eadie, Hyldgaard-Jensen, Mann, Reid & Whitelaw, 1970) but smaller changes in VFA proportions do not bear any simple relationship to the balance of bacterial species (Latham, Sharpe & Sutton, 1971). …”
mentioning
confidence: 99%